Two-step-index ZnMgTe/ZnTe Waveguide Structures with Improved Crystal Quality. Issue 23 (15th February 2016) - Sun, Wei-Che; Kazami, Fukino; Wang, Jing; Nakasu, Taizo; Hattori, Shota; Kizu, Takeru; Hashimoto, Yuki; Kobayashi, Masakazu; Asahi, Toshiaki
ABSTRACT: ZnMgTe(Cladding)/ZnTe(Core)/ZnMgTe(Cladding) thin film waveguide had been grown by molecular beam epitaxy (MBE) and presented a great potential to be a high performance Electro-optical (EO) modulator. For a low propagation loss ZnMgTe/ZnTe waveguide, thick cladding layer with high Mg composition (Mg %) is needed. However, the in-plane lattice mismatch of the fabricated device with high Mg % and thick cladding layer was large. It might cause the cladding/core interface roughness and asperities due to the misfit dislocation, and degrade the device performance. Because EO property of waveguide device is primarily influence by the structure thickness, the device efficiency improvement in this study was only considered to reduce the defects asperities that would cause propagation loss without decreasing the Mg % or the total thickness of the cladding layers. Therefore, we introduced a low Mg % layer between the cladding and the core layer to circumvent the effect of large lattice mismatch. The in-plane lattice mismatch of the devices was monitored using reciprocal space mapping, and surface morphologies were also observed using atom force microscope. The two-step index ZnMgTe/ZnTe waveguide had shown to have lower degree of relaxation compared to that of single-step index waveguide device with close Mg % and cladding layer thickness. Therefore, the crystal degradation of the two-step-index waveguide caused by lattice mismatch was successfully suppressed by introduction extra low Mg % layers. The morphologies of the two kinds of waveguide structures have similar surface asperities, which indicated the extra inserted layers did not produce additional large scale asperities at the interfaces that would increase the propagation loss.